Asthma Education in the Student Laboratory. (February 2013) - Thurmon, Tara B.; Schwartz, Lorie L.; Jervis, Kelly P.
The Integrated Pharmacy Skills Laboratory (IPSL) at South University School of Pharmacy is dedicated to providing future pharmacists with the necessary knowledge and skills to care for asthma patients. Asthma is a chronic respiratory disorder that is characterized by airway inflammation, hyper responsive airways, and bronchoconstriction. It affects more than 30 million people and accounts for $30 billion in health care costs. Therefore, it is vital for our students to be educated in asthma management including medications and devices to improve patient outcomes. Students, as future pharmacist, learn to manage asthma patients in the community setting, the hospital setting, and the clinic setting through various laboratory experiences.